Efektivitas Pemberian Limbah Biogas Sapi Terhadap Kadar Protein Jerami Jagung Untuk Pakan Ternak - Sari Widya Utami; Ari Kristiningsih (Politeknik Negeri Cilacap, 2021)
Plant-livestock integration was one of the concepts of integrated agriculture. Agricultural waste had the potential to be developed as animal feed material, such as corn straw. The availability of waste, such as agricultural, livestock and biogas wil pollute the environment if it is not utilized. Therefore, the purpose of this study was to determine the effect of giving biogas waste on the protein content of corn straw, as a by-product of corn cultivation. The treatment in this study used two factors, namely (i) cow biogas solid waste consisting of 2 treatment levels, namely 0 and 5.4 tons/ha, and (ii) cow biogas liquid waste consisting of 4 treatment levels, namely 0 liter/ha. , 500 liters/ha, 1000 liters/ha and 1500 liters/ha. The data measured were nitrogen content, nitrogen absorption and protein content of corn straw. The results showed that the application of biogas waste was able to increase the protein content of corn straw.